A consolidação da crise da literatura no ensino médio - Pereira, Edineia de Lourdes (2013)
In this research we analyze the crisis of the literature in High School. Our objective is to structure the discourse of agents who have sought to understand and troubleshoot the process of losing symbolic power of literature in the schools. Thus, the analysis of the corpus has prepared speeches in which agents seek to understand this crisis. Considering that culture and education are part of the social representations and are complex structural systems built over time, we conducted an archeology supported the conceptualization of Michel Foucault, in order to understand how this was a tradition appraiser crises. From this plan of action, we trace a path through the speeches of textbooks and school anthologies of Brazilian literary, speeches by education researchers linked to Literary Studies and the speeches of regulators High School. We look, therefore, map the habitus of agents of Brazilian literary field in relation to the fact that the gradual loss of the symbolic power of literature in school. Our hypothesis is that this habitus has prevented agents of teaching of literature – as this teaching is done – recognize that literature has lost its position and its function, i.e. part of its usefulness to the contemporary society.